The Model of Innovative Activities Management in a Competitive Market Conditions - Nabiullina, Karina R.; Nikolaeva, Aleksandra N.; Egorova, Ekaterina G.; Malova, Elena. A.; Petrova, Elena V.; Antipova, Elena. A.; Belov, Georgy L.; Vasilyeva, Larisa G. (International Journal of Economics and Financial Issues, 2016)
Market competition in all sectors of the economy calls for maximum use, activation, optimal implementation of the results of scientific and technical progress - innovations. This is necessary not discrete implementation of innovative projects and development of a new system of interaction of innovative processes in all areas. Purpose of the article is modeling of innovative activities' processes management and development of recommendations to improve its productivity. The authors analyzed the theoretical and methodological aspects of innovative activities' implementation, revealed the structure of innovative activities and the parameters of its implementation. A mathematical model for innovative activities' managing, defining the hierarchy of its connections is proposed. This article is intended for regional leaders, top managers of enterprises, scientists and researchers involved in the innovative development of an economic sector. Keywords: innovations, innovative activities, management, modeling, investment JEL Classifications: Ð¡15, Ð¡51, O31